Prevalence of Chumydia trachomatis e Neisseria gonorrhoeae by PCR in urine samples of pregnant adolescents and women seen at gynecology outpatient unities in Porto Alegre, Brazil - Ramos, Mauro C; Becker, Daniela; Germany, Cíntia; Ritter, Anelise T; Perin, Márcio Túlio; Sander, Melissa Acauan; Filgueiras, Absalom L; Cestari, Tânia (Brazilian Journal of Sexually Transmitted Diseases, 2002)
[...]